Evaluation of physicochemical and biological properties of nonreconstituted MYL-1401O vials, reconstituted MYL-1401O suspension in vial, and diluted MYL-1401O suspension in infusion bags (0.9% saline) for extended duration. (1st February 2022) - Vats, Bhavesh; Goyal, Parag; Mathew, Zacharia; Ghosh, Ranendu; Babu, Moram Narendra; Jadav, Rahul Singh; Nair, Arya M.; Subbarao, Malini; Bera, Arnab; Prakash Sadasivappa, Kirthi; Kabadi, Pradeep; Sarkar, Anindya; et al.
ABSTRACT: Background: MYL-1401O; trastuzumab-dkst (Ogivri™; Mylan Inc.) is a biosimilar to the trastuzumab reference product (Herceptin®; Genentech, USA). Assessment of physicochemical stability and biological activity for the non-reconstituted, reconstituted, and infused solution over an extended, clinically relevant duration is critical for ensuring optimal patient outcomes and health resource utilization. Methods: The physicochemical and biological stability of MYL-1401O was assessed in non-reconstituted vials stored at 25 °C ± 2 °C/60% ± 5% relative humidity (RH) for 6 months, reconstituted 21 mg/mL solution in vials stored at 2 °C to 8 °C for 10 days, and diluted in 0.9% saline-containing infusion bags at 0.3 mg/mL and 4.0 mg/mL stored for 77 days at 2 °C to 8 °C, plus an additional 2 days at 25 °C ± 2 °C/60% ± 5% RH. Results: At all storage conditions tested, MYL-1401O was physicochemically and biologically stable for extended duration and under various temperature and humidity conditions. Conclusions: MYL-1401O retained its physicochemical and biological stability under different storage conditions, which supports advanced preparation of MYL-1401O, better efficiency, less wastage, and cost-savings for better patient management.